NARRATIVE STRUCTURES AND MYTHOLOGICAL THEMES IN MODERN AMERICAN FANTASY AND A STUDY OF C.S. LEWIS’ INFLUENCE - Rakhmatullayeva Mahliyo Kholkhuja qizi (Bright Mind Publishing, 2025)
This study examines the role of mythopoeic world-building in contemporary American fantasy literature, focusing on the influence and enduring legacy of C. S. Lewis. It explores how Lewis’s narrative techniques such as portal fantasy, mythological integration, and thematic depth have shaped the genre’s development. Using a qualitative literary analysis method, the study compares The Chronicles of Narnia with selected works by modern American fantasy authors, including Neil Gaiman, Rick Riordan, and Brandon Sanderson. The results indicate that Lewis’s influence remains evident in contemporary fantasy through symbolic storytelling, moral allegories, and mythological synthesis. The discussion highlights the evolution of mythopoeic world-building and its continued relevance in modern speculative fiction. This research contributes to understanding the progression of fantasy literature and the lasting impact of C. S. Lewis on the genre.
Keywords: Mythopoeic world-building, contemporary American fantasy, portal fantasy, mythology in literature, narrative techniques, speculative fiction.